Implementation of Interior Design Project Monitoring Application using Appsheet (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
To achieve project success, careful and continuous monitoring of progress, resources, and potential risks is essential in this context. A real-time application-based project monitoring system has been developed and implemented. This system is designed to provide comprehensive project visibility, making it easier for staff to monitor task progress, resource utilization, and proactively identify potential problems. With an intuitive, responsive, and communicative application interface, it makes performance more efficient between office staff and field teams. The results of this study prove that this application system is a very valuable tool for ensuring that projects are completed on schedule and within budget at PT. Generasi General Contractor. The project monitoring application with the waterfall method is a very classic method and its main characteristic is a linear and structured workflow. Where each stage must be completed before moving on to the next stage without the opportunity to return to the previous stage. This method is very suitable to be developed into a project monitoring application. And the results of usability testing using the single ease question (SEQ) method were tested with 10 questions selected based on experience in using the application. The results of the Usability testing from each staff showed a positive response with an average SEQ score of 5.31. Proving that the project monitoring application helps in reducing the problems that exist at PT. Generasi General Contractor.